Digital Transformation Analysis in the Manufacturing Module in Aluminium Companies using the TAM Method (Journal of Advances in Information Systems and Technology, 2023)
This research was conducted to identify the factors affecting the success of digital transformation through the use of the manufacturing module in aluminum companies. The Technology Acceptance Model (TAM) method was used to measure technology acceptance through the use of the manufacturing module with variables of perceived usefulness (PU), perceived ease of use (PEOU), and perceived risk (PR) that affect the behavioral intention of use (BIU) at PT. Allure Allumunio and the success of digital transformation were measured through descriptive analysis. The sample was taken using the entire population with a total of 50 manufacturing module users. The collected data was analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.8 software. A total of 48 respondents with valid data were obtained and validity and reliability tests were performed, resulting in valid and reliable instruments. The R-square, Q-square, and t-test were used to analyze the proposed hypothesis. The results showed that three hypotheses were accepted: PU > BIU, PEOU > BIU, and PEOU > PU, and one hypothesis was rejected: PR > BIU because risk did not have a significant impact on the behavior intention of technology acceptance. Additionally, the analysis of digital transformation success was conducted with results showing an increase in company productivity and a decrease in risk, marked by an increase in units received on time after digital transformation and a 78% level of adaptation satisfaction. The conclusion is that technology acceptance was achieved through perceived usefulness and perceived ease of use, as well as increased productivity, level of adaptation satisfaction, and decreased risk, which are factors contributing to the success of the digital transformation.